Kajian Tingkat Bahaya Erosi Pada Berbagai Tipe Penggunaan Lahan di Kecamatan Merdeka Kabupaten Karo - Parlin Hotmartua Putra Pasaribu; Abdul Rauf; Bejo Slamet (Jurnal Serambi Engineering, 2018)
The purpose of this study is to determine the level of erosion in various types of land use in Merdeka District. This research used erotic prediction analysis survey method with Universal Soil Loss Equation (USLE) method. The parameters measured in this research are erosivitas, erodibility, length and slope of the slope, cover vegetation, conservation measures, soil effective depth, soil density. The techniques of collecting and analyzing the research data are: making of land unit, field data collection, rainfall data analysis, soil analysis, and map analysis. The results showed that the rate of erosion in Merdeka District was 13,250,049 ton / ha / year with average erosion rate reached 1,261,909 ton / ha / year. The highest erosion rate was found in land use area of 2,959,018 tons / ha / year, while the lowest erosion was found on the use of settlement land of 29,810 tons / ha / year.